STRATEGI PENGADAAN BAHAN BAKU PAKAN IKAN BERBASIS PRODUK SAMPINGAN AGRIBISNIS PADA CV BABELAN AGRO SEJAHTERA BEKASI - Rahmanto, Muhammad Ikhwan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2013)
Supply of raw material of fish feed unstable causing the company is not easy to develop fish feed business cheap and quality. The purpose of this study was to produce raw material procurement strategy formulation based agri-products in order to anticipate the instability of raw material supply of fish feed. The method used was a case study at CV. Babelan Agrosejahtera (CV. BAS) Bekasi. Data collected by the company to the observation, secondary data analysis, in-depth interviews with managers. Analyzed using Matrix Internal External (IE) and SWOT Matrix Analysis. IE matrix analysis showed that the raw material management CV BAS position IV cells, meaning describes the position grow and build. Companies need to do a backward integration by improving supply chain management, especially its relationship with suppliers. Furthermore SWOT analysis resulted in five strategy formulation of fish feed raw material supply on the CV. BAS is as follows: (a) development of alternative of raw materials to cheao and quality, (b) increased cooperation with suppliers, (c) integrated Quality Control of Raw Materials, (d). Improve stability of raw material supply, and (e) Improvement warehouse management.